Single-nucleus RNA-seq reveals no increase in T cells in Alzheimer’s disease prefrontal cortex or hippocampus - Oxendine, Jake D.; Sirkis, Daniel W.; Jonson, Caroline; Yokoyama, Jennifer S. (Frontiers in Cellular Neuroscience, 2025)
BackgroundAlzheimer’s disease (AD) has long been associated with hallmark protein aggregates, yet increasing evidence suggests immune involvement may contribute to its progression. Prior studies have found increased T cell presence in AD brain tissue, raising the possibility of neuroimmune crosstalk.MethodsWe used single-nucleus RNA sequencing data from the Religious Orders Study and Memory and Aging Project (ROSMAP), the largest available postmortem AD cohort, to investigate T cell dynamics in prefrontal cortex (PFC) and hippocampus.ResultsContrary to prior findings, we observed no significant increase in T cell frequency in individuals with pathologically confirmed AD in either region. We replicated these findings in dorsolateral PFC (DLPFC) using the Seattle Alzheimer’s Disease Brain Cell Atlas (SEA-AD). Notably, although we confirmed a prior finding of T cell expansion in middle temporal gyrus (MTG), the strength of this association was affected by donor age. Additionally, we detected no change in gene expression in T cells in the brain parenchyma from individuals with AD.ImpactThese results suggest that T cell enrichment in AD may be regionally restricted and not as widespread as previously assumed. Our findings underscore the importance of brain region selection, analytical approach, and dataset composition in interpreting immune cell dynamics in neurodegenerative disease.